Rethinking about the values transmission in textbooks for children by means of illustrations - José Gijón Puerta; Estrella Fages (Journal for Educators, Teachers and Trainers, 2010)
The Spanish society has changed deeply during the last decades, and these changes have its reflection in all the social aspects. Textbooks and infantile books are not an exception, and the values that are transmitted by them are extremely important for the integral formation of children and young people. In this respect, illustration has a fundamental role in the creation and modification of social stereotypes, and this must be born in mind at the moment of selecting school texts and complementary readings by teachers.